2016
DOI: 10.3390/rs8070540
|View full text |Cite
|
Sign up to set email alerts
|

Do Red Edge and Texture Attributes from High-Resolution Satellite Data Improve Wood Volume Estimation in a Semi-Arid Mountainous Region?

Abstract: Remote sensing-based woody biomass quantification in sparsely-vegetated areas is often limited when using only common broadband vegetation indices as input data for correlation with ground-based measured biomass information. Red edge indices and texture attributes are often suggested as a means to overcome this issue. However, clear recommendations on the suitability of specific proxies to provide accurate biomass information in semi-arid to arid environments are still lacking. This study contributes to the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…The vegetation indices used in this study were chosen based on their optimal performance in literature [17,22]. Formulae for computing vegetation indices are detailed in Schumacher et al [38]. The window sizes for deriving the grey-level co-occurrence texture models used in this study were 3 × 3, 5 × 5 and 7 × 7 pixels [39,40].…”
Section: Modelling Above-ground Grass Biomassmentioning
confidence: 99%
See 3 more Smart Citations
“…The vegetation indices used in this study were chosen based on their optimal performance in literature [17,22]. Formulae for computing vegetation indices are detailed in Schumacher et al [38]. The window sizes for deriving the grey-level co-occurrence texture models used in this study were 3 × 3, 5 × 5 and 7 × 7 pixels [39,40].…”
Section: Modelling Above-ground Grass Biomassmentioning
confidence: 99%
“…The texture models computed in this study were mean, variance, homogeneity, contrast, dissimilarity, entropy, second moment and correlation. More details about the formulae for computing these texture models are summarised in Dube and Mutanga [30], as well as Schumacher et al [38]. All the variables used in this study, and the formulae used to compute them, are detailed in Table 2.…”
Section: Modelling Above-ground Grass Biomassmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we applied VHR RapidEye data comprising a red edge channel that was centered at 710 nm. Recent studies have shown the performance of red edge bands in facilitating important information on the state of vegetation and their benefit for vegetation monitoring [29][30][31]. In 2015, Sentinel-2A satellite has been launched.…”
Section: Introductionmentioning
confidence: 99%